Local Children Fill Cast of Favorite Fairy Tale (Raton, NM Raton Range, 1997)
Article is promoting Cinderella giving information about the cast.
Newspaper Article + Photograph of Scott Minor and Amy Pettigrew g
Master list item #: 83
File location is in the Raton file Cabinet
Keywords: Minor, Scott -- Director; Pettigrew, Amy -- Director; Herrera, Ashley -- Student Actor; Crossley, Emilie -- Student Actor; Esquibel, Stancie -- Student Actor; Wright, Mary -- Student Actor; Cornay, Matthew -- Student Actor; Missoula Children's Theater -- Performance group; McCune Foundation -- Sponsor; Raton Builder Supply -- Sponsor; Dairy Queen -- Sponsor; Raton Kiwanis -- Sponsor; Plays; Live Performance; Student Theater; Art Promotion; Shuler Theater; Raton, New Mexico